Reconstruction Of The Understanding Of Polygamy In Islam: Analysis Of Nasaruddin Umar's Hermeneutics Of Gender Justice - Nurramadhani, Fatimah Azzahra; Paizin, Harel Bayu (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Polygamy is an Islamic family law issue that continues to be debated, especially when its practice in modern Muslim societies often leads to gender inequality. Although it has a normative basis in the Qur'an, specifically QS. al-Nisā' [4]: 3 and QS. al-Nisā' [4]: 129, verses on polygamy are often understood textually as legal justification, without considering the historical context and ethical objectives. As a result, there is a gap between the moral message of the Qur'an, which emphasizes justice and benefit, and the social reality of polygamy, which is fraught with gender inequality. This study aims to reconstruct the understanding of polygamy in Islam through an analysis of Nasaruddin Umar's hermeneutics of gender justice, as well as to examine the contribution of his thoughts in bridging the gap between the text of the Qur'an and social practice. This research is a library-based qualitative study. Primary data were obtained from the Qur'an and the works of Nasaruddin Umar. Secondary sources include academic books, journal articles, and previous research relevant to the theme of polygamy and gender interpretation. Data collection techniques. Data collection was carried out through systematic literature searches in both physical libraries and electronic databases, and the data were analyzed using descriptive-qualitative methods and hermeneutic analysis, considering the historical, social context, and moral objectives of religious texts. The results of the study show that Nasaruddin Umar interprets the verses on polygamy as contextual and preventive social regulations, not as an ideal marriage institution. Justice in polygamy is understood not only in material terms, but also encompasses emotional and psychological dimensions that are theologically difficult for humans to achieve. Therefore, polygamy is positioned as a very strict conditional permission, while monogamy is considered more in line with the objectives of Sharia law, namely justice, protection of human dignity, and family welfare. This study contributes to the development of Qur'anic exegesis and gender studies by emphasizing the importance of a hermeneutic approach oriented towards substantive justice in understanding the verses on polygamy, thereby producing a more humanistic, proportional, and relevant understanding in the context of contemporary Muslim society.